City utility tunneling designing method based on “support-rock mass” interaction - Duyen Phong Nguyen; Trung Thanh Dang; Tuan Minh Tran; Van Thinh Nguyen (Горные науки и технологии, 2018)
At present time, megacities face acute problem of construction of tunnels for laying utility networks. In such large cities as Hanoi, Ho Chi Minh, there are still no solutions to the problem of laying technical pipelines, power cables, water supply and sewage pipelines. The paper describes the method of utility tunnel designing, taking into account rock composition and restricted construction conditions for each specific area, based on the use of small tunnel-boring machine. Using this method ensures reliability and economic feasibility of the tunnel construction project.